Pengaruh Penambahan Serat Nylon terhadap Kinerja Beton - Adianto, Yohanes L.D.; Basuki, Tri (Department of Civil Engineering, Diponegoro University, 2004)
Concrete is composite material composed by aggregate and covered by portland cement matrix filled the spaces among particles, which makes a solid material. One of the important properties of concrete is ductility. Low ductility of concrete is presented by stress-strain curve, which has fast decrease of compressive strength in post peak load area, so collapse happen in relatively immediate. Nylon fiber has lower modulus of elasticity than concrete. The using of fiber is expected able to produce concrete more ductile. The objective of this research is to explore the effect of one kind polymeric fiber, nylon, in normal concrete (fcâ€™= 30 MPa). The result shows that there is no significance difference in compressive and flexural strength in concrete with varied nylon fiber content, but there is significance difference in compressive strength among varied age of concrete. There is significance difference in modulus of elasticity of concrete. The modulus of elasticity will increase in line with the decrease of nylon fiber content.Â This research show that higher fibre content added to the concrete, the concrete will show higher strength in cyclic loading.Key words: nylon, fibre, normal concrete, compressive strength, flexural strength, modulus of elasticity.